Terrestrial cue learning and retention during the outbound and inbound foraging trip in the desert ant, Cataglyphis velox - Freas, Cody A.; Spetch, Marcia L. (Journal of Comparative Physiology, 2019)
Foraging ants are able to acquire and retain long-term memories of panorama cues around the nest and along known routes. Here we explore foragers’ ability to learn and retain skyline cues experienced on only the outbound or inbound portion of the foraging trip. Foragers exposed to the skyline on the outbound portion showed single trial learning of these cues. Furthermore, the navigational performance of these “Outbound-Only” foragers was on par with foragers that experienced the full route. In contrast, foragers experiencing the skyline only on the inbound portion, “Inbound-Only” foragers, took 5 trips to successfully learn these cues. These performance differences persisted for long-term memory retention. Outbound-Only foragers successfully oriented after a 3-day delay and showed similar performance to the full route control, whereas Inbound-Only foragers were no longer able to orient successfully to these cues after 3 days. Additionally, long-term memory formation of skyline cues appears to require multiple presentations, as foragers with only one outbound experience of the skyline could not successfully orient after the delay. Our results suggest that terrestrial cue learning and retention is more robust when cues are experienced on the outbound segment of the foraging trip.